PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN PADA GURU TK NEGERI KINTAMANI, BALI - Elizabeth Prima; Christiani Endah Poerwati; Putu Indah Lestari; I Made Elia Cahaya; Ni Made Ayu Suryaningsih; Ni Luh Rimpiati (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
The Covid-19 pandemic made the teaching and learning process unable to run properly. Activities involving many people are not carried out to prevent the spread of the Covid-19 virus. This has an impact on the teaching and learning process in Kintamani State Kindergarten located on Kintamani Highway, Kintamani Village, Kintamani District, Bangli Regency, Bali Province. During learning from home (BDR) teachers have difficulty in providing learning materials. Teachers are only able to send tasks that will be done by children through the Whatsapp group application without being equipped with learning videos that can be received and learned by children at home. The lack of teacher knowledge about how to make learning in the format of learning video becomes the basis of thinking why PKM Prodi is carried out. The subjects of this PKM are teachers in Kintamani State Kindergarten. The method used in this PKM is the assistance of making learning videos that are implemented by applying health protocols. The purpose of PKM Prodi is to train and accompany kindergarten teachers in making learning videos ranging from the process of shooting, editing, to uploading on the school's YouTube channel so that it can be shared and studied by students. The result of the evaluation of training and mentoring activities is that teachers are able to make learning videos and upload them on school YouTube. Thus, teachers are no longer constrained during the implementation of the teaching and learning process even though students learn from home (BDR). Keywords: training, learning videos, kindergarten